Study the effect of environmental noise on infrared Tx-Rx circuit signals - Mohd Zaihan Ibrahim
This final year project is about the environmental noise effecting infrared transmitter and receiver (TX-RX) circuit signal. Efforts on environmental noise reduction are also proposed. To improve the noise immunity against ambient light, the optical noises from the fluorescent lamp are analyzed and the behavior of an Amplitude Shift Keying (ASK) infrared communication link is modeled under these noises.